Migrating applications from microsoft DNA to IBM WebSphere - Oguejiofor, Edward (IBM redbooks., 2005)
This IBM Redbooks publication is about migrating your application from Microsoft DNA to IBM's WebSphere, from coming up with a strategy and scope for the migration to architecting and developing the migration solution. If you are the IT decision maker or the project manager who is responsible for setting the scope and defining the strategy for your migration, then the first part of this book is aimed at you. The second part of the book focuses on IT architects, IT specialists, or programmers who have to re-engineer, design, code, and test the migration solution. Part 1 focuses on what to do before you commence the migration, and how to set the scope within the migration constraints and come up with your migration strategy. In Part 2 we look at redesigning the architecture of your Windows DNA application, and discuss how to identify the considerations unique to your migration scenario and provide guidelines for migrating the different tiers of your application based on your migration strategy and redesigned architecture.